PEMBACAAN DEKONSTRUKTIF ATAS RELASI AL-QUR’AN DAN BUDAYA: Studi Apresiatif-Kritis atas Pemikiran Nashr Hamid Abu Zayd dan Aksin Wijaya - Aldi Hidayat (Academic Journal of Islamic Principles and Philosophy, 2023)
Naṣr Ḥāmid Abū Zayd and Aksin Wijaya argued that the textuality of the Qur'an in the sense that the Qur'an, like other texts, cannot be separated from the cultural situation in which it was revealed. Just as the text certainly contains cultural content, the Qur'an also contains Arab cultural content from the 7th century AD. This idea triggers pro and contra responses, but it is rare – if not to say not – to find an accurate critical response. Researchers who support this do not balance their appreciation with criticism. On the other hand, researchers who reject this idea submit inaccurate responses, because they use a theological approach, even though the argument of these two thinkers have a philosophical-linguistic nuance. This article aims to fill the gap in accurate criticism of the idea of the textuality of the Qur'an. This article criticizes the thinking of the two figures in advance with the same knife, namely the philosophy of language. We will use Derrida's deconstruction as a critical knife for both of their thoughts. Therefore, this article has two problem formulations as an agenda. First, what do the two figures above think about Qur'an? Second, what is the ambiguous point in their thinking regarding the Qur'an? This article will culminate in two conclusion. First, recognize quasi-objectively their thinking by basing understanding on the philosophical linguistic arguments they offer. Second, philosophically emphasizing that Arab culture has not infiltrated the Qur'an.